ISOTOPIC COMPOSITION OF VARIOUS FORMS OF CARBON IN ECLOGITE FROM KIMBERLITE OF THE MIR PIPE - Galimov E.M.; Solov'yeva L.V.; Belomesnyy A.B. (My University, 1989)
Investigating the isotopic characteristics of carbon in eclogite from kimberlite is of interest both for identifying the character of the eclogite material itself and for investigating the fractionation of carbon under plutonic conditions. We made a detailed study of the isotopic composition of various forms of carbon in a xenolith of graphitic eclogite from the kimberlite of the Mir pipe. The eclogite contained about 45 percent orange garnet (3 to 5 mm), approximately 55 percent dull green clinopyroxene (3 to 8 mm), and 1 to 3 percent scattered flakes of graphite measuring 0.5 to 3 mm, less often 5 to 8 mm. The clinopyroxene is highly altered, as manifested by the occurrence of whitish decomposition products, particularly in the edges of the grains. Among the secondary minerals, developed in the interstices we found fine-grained carbonate and serpentine. Chemically, the minerals in the specimen are magnesian-iron eclogites. In the Mir pipe this type of eclogite is usually diamond-bearing.